(untitled) (Journal of Pharma Insights and Research, 2026)
Natural intercellular communication relies heavily on exosomes, a subset of endosome-derived extracellular vesicles ranging from 30 to 150 nm in diameter. These biogenic nanovesicles facilitate the transfer of functional proteins, lipids, and diverse RNA species between distant cell populations, maintaining physiological homeostasis and influencing pathological progression. The inherent biological origin of exosomes confers superior advantages over traditional synthetic delivery systems, specifically regarding biocompatibility, extended systemic circulation, and minimal immunogenic profiles. Their intrinsic ability to bypass formidable biological barriers, such as the blood-brain barrier, positions them as ideal candidates for treating complex neurological and oncological conditions. Advanced engineering techniques now allow for the precise modification of exosomal surfaces and the encapsulation of diverse therapeutic cargoes, including small-molecule drugs and nucleic acids. Despite these promising attributes, the transition from laboratory-scale research to clinical application faces significant hurdles related to standardized isolation protocols, large-scale manufacturing scalability, and stringent regulatory requirements. Optimization of loading efficiencies and the development of high-yield production cell lines remain critical areas of focus. Combining biotechnology with nanotechnology offers the potential to refine these vesicles into highly targeted, personalized therapeutic agents. Resolving current technical limitations will facilitate the integration of exosome-mediated delivery into routine clinical practice, representing a transformative shift in precision medicine and targeted therapeutics